Comparative analysis of primary versus secondary paranasal sinus mucoceles: a case control study - Le Tran Quang Minh; Nguyen Thanh Tuan; Nguyen Minh Hao Hon (The Egyptian Journal of Otolaryngology)
Abstract Background Paranasal sinus mucoceles are benign cystic lesions characterized by mucous accumulation that can lead to significant complications due to erosion of sinus walls and compression of adjacent structures. This retrospective study aims to compare the clinical characteristics and treatment outcomes of primary and secondary mucoceles. Methods We reviewed medical records of 68 patients treated for mucoceles at the Ear, Nose, and Throat Hospital in Ho Chi Minh City, Vietnam, from June 2022 to June 2024. Advanced diagnostic imaging techniques, such as computed tomography (CT) and magnetic resonance imaging (MRI), were utilized in the management of these lesions. Statistical analysis was conducted using chi-square and t-tests to compare the characteristics and outcomes between the two groups. Results The study found that primary mucoceles often presented with less severe symptoms compared to secondary mucoceles, which occur post-surgery or post-trauma and are associated with more severe symptoms and complications. Primary mucoceles were most frequently located in the frontal-ethmoid region (47.4%), while secondary mucoceles had a similar distribution but were more prevalent following previous surgical interventions. Endoscopic sinus surgery was the primary treatment for both groups, with secondary mucoceles frequently requiring more complex surgical interventions. Postoperative improvement was significant in both groups, though secondary mucoceles exhibited slower recovery and higher rates of residual minor visual impairments. Conclusion The comparison between primary and secondary paranasal sinus mucoceles reveals critical differences in clinical profiles and treatment outcomes. Understanding these differences is essential for optimizing management strategies and improving prognosis for patients with these challenging conditions. Further research is needed to explore long-term treatment effects and the efficacy of different surgical approaches.